Emergence and Embodiment in Economic Modeling - Mousavi, Shabnam; Sunder, Shyam (Frontiers in Psychology, 2022)
Eternal curiosity about what lies in the adjacent layers of the disciplinary onion of science does not allow scientific thinking to remain confined to a single layer of observed phenomenon. Diffusion of inquiry into adjacent layers may take the form of either embodiment (which focuses on links to the contents of the inner layers or component parts), or emergence (which looks outwards). Embodiment explores what aspects of a phenomenon of interest might arise from the properties of the constituent elements, such as seeking an understanding of cognition in terms of neurobiological endowments. Emergence takes the reverse direction by examining how complex interplay among elements at one level may give rise to distinct aggregate level phenomena with properties absent in the parts. Patterns of movement of schools of fish and the outcomes of markets are among examples of easily observable emergent phenomena. We introduce a three-tier framework that represents embodiment as an inward deployment of scientific principles and emergence as an outward framing of observations from inanimate to animate to sentient existence. Viewed in this framework, embodiment and emergence simply represent two directions of investigation, each yielding distinct insights. This paper explains how taking an outward direction recasts long-lasting debates over reductionism, methodological individualism and the role of optimization in the study of human behavior, and hints at new questions regarding the social phenomenon.